A regulação no mercado de planos de saúde: a ação do consumidor e a estratégia da Agência Nacional de Saúde Suplementar - ANS - Barone, Sônia Regina de Mesquita (2003)
The scope of this dissertation is to assess the attitudes of subscribers to private health insurance schemes and the regulatory strategy of the Ancillary National Health Agency -- ANS in relation to their demands. The ancillary health market features various players, each with their own specific interests and priorities. Consequently, the ANS should strive to maintain the balance between the consumers, the economic intermediaries and the State, ensuring that the Agency's powers to establish norms, as well as to regulate and to supervise each be exercised independently. Many people contend that there are elements not currently incorporated into the current services of the ANS which could contribute to its regulatory strategy. This study was conducted from the standpoint of theories applied to State administration for structural analysis of the ANS and its strategies, in addition to a symbolic and rational approach for a better understanding of the consumers involved. A survey was conducted of existing records of the ANS, as well as data collected from direct observation. Analysis of the data obtained led to the conclusion that the consumer can become a close ally in the regulatory activity of the ANS, to the extent that the latter may acquire more in-depth knowledge of aspects contained in the demands of the former.